Globalization, Global Political Economy and Technical and Vocational Education and Training: A Nexus - Acharya, Sabitri Devi (Journal of Technical and Vocational Education and Training, 2023)
The paper explores the understanding of globalization, global political economy, and their relation with Technical and Vocational Education and Training (TVET) by utilizing the critical discourse analysis method as suggested by Fairclough. Several themes, such as globalization, global political economy, political ideology, national and international labor market, TVET policy, and curriculum for skill development are identified and tried to make connections among them. The findings indicate that globalization and global political economy influence the national economic policy and demand for and supply of labor-related policy. Nepal is a major labor-sending country for foreign employment. Supply of labor is directly related to TVET. TVET has been contributing to the preparation of basic- and mid-level human capital. It indicates the production of semi-skilled human resources for the low-paid international labor market. There are many other issues, including occupation risk, exploitation, working condition, and social and cultural relations in the context of the international labor market. Current TVET policy and curriculum are not sufficient to address these problems.